Chemical ecology and phytochemistry of forest ecosystems - Romeo, John T. (Recent advances in phytochemistry, 2005)
The Phytochemical Society of North America held its forty-fourth annual meeting in Ottawa, Ontario, Canada from July 24-28, 2004. This year's meeting was hosted by the University of Ottawa and the Canadian Forest Service, Great Lakes Forestry Centre and was held jointly with the International Society of Chemical Ecology. All of the chapters in this volume are based on papers presented in the symposium entitled "Chemical Ecology and Phytochemistry of Forest Ecosystems". The Symposium Committee, Mamdouh Abou-Zaid, John T. Arnason, Vincenzo deLuca, Constance Nozzolillo, and Bernard Philogene, assembled an international group of phytochemists and chemical ecologists working primarily in northern forest ecosystems. It was a unique interdisciplinary forum of scientists working on the cutting edge in their respective fields. While most of these scientists defy the traditional labels we are accustomed to, they brought to the symposium expertise in phytochemistry, insect biochemistry, molecular biology, genomics and proteomics, botany, entomology, microbiology, mathematics, and ecological modeling. * A collection of papers presented at the 44th Annual meeting of the Phytochemical Society of North America * Representation from a unique interdisciplinary forum of scientists * Includes discussions on new genomics research in forest health